Online Registry for Nationwide Database of Current Trend of Helicobacter pylori Eradication in Korea: Interim Analysis - Kim, Beom Jin; Kim, Hyun-Soo; Song, Hyun Joo; Chung, Il-Kwun; Kim, Gwang Ha; Kim, Byung-Wook; Shim, Ki-Nam; Jeon, Seong Woo; Jung, Yun Jin; Yang, Chang-Hun; Kim, Ji Hyun; Kim, Tae Ho; et al. (Journal of Korean medical science, 2016)
Eradication of Helicobacter pylori using first-line therapy is becoming less effective. Subjects who had been treated for H. pylori infection were prospectively enrolled through an on-line database registry from October 2010 to December 2012. Demographic data, detection methods, treatment indication, regimens, durations, compliance, adverse events, and eradication results for H. pylori infection were collected. Data of 3,700 patients from 34 hospitals were analyzed. The overall eradication rate of the first-line therapy was 73.0%. Eradication failure was significantly associated with old age, concomitant medication, and comorbidity. Regional differences in eradication rates were observed. The most common first-line therapy was proton pump inhibitor-based triple therapy (standard triple therapy, STT) for 7 days (86.8%). The eradication rates varied with regimens, being 73% in STT, 81.8% in bismuth-based quadruple therapy, 100% in sequential therapy, and 90.3% in concomitant therapy. The eradication rate in treatment-naïve patients was higher than that in patients previously treated for H. pylori infection (73.8% vs. 58.5%, P < 0.001). The overall eradication rate for second-line therapy was 84.3%. There was no statistical difference in eradication rates among various regimens. H. pylori eradication rate using STT is decreasing in Korea and has become sub-optimal, suggesting the need for alternative regimens to improve the efficacy of first-line therapy for H. pylori infection.